PENERAPAN 4C SKILLS DALAM PEMBELAJARAN ABAD 21 DI SEKOLAH DASAR - Realitawati Realitawati; Fadhli Dzil Ikrom; Endang Herawan; Deni Kadarsah (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
Elementary schools play an important role in developing students' understanding and skills. Therefore, the transformation of elementary schools is very important to produce a critical, creative and innovative generation capable of facing the challenges of the 21st century. The purpose of this research is to determine the application of 4C skills (Critical Thinking Skills, Creativity and Innovation Skills, Communication Skills, Collaboration Skills) in teachers' teaching in 21st century learning at SD Negeri Serang 20. The research method uses qualitative methods by conducting structured interviews. The target respondents were all 10 teachers of SD Negeri Serang 20. The results of the research show that the respondents have integrated 4C skills into the curriculum and daily learning activities.